Lenin and the national question. Beyond essentialism and constructionism - Castien Maestro, Juan Ignacio (Nómadas. Critical Journal of Social and Juridical Sciences, 2016)
Lenin’s analysis of the ’national question’ shows numerous virtualities from a theoretical and political perspective. We are going to examine some of the theoretical conceptions which seem to underlie his view on the national question. In our opinion, these conceptions are a commendable work since they represent an alternative to the dilemma of essentialism and constructivism through which the social contemporary thinking has often fluctuated. Whereas essentialism tends to consider the national fact as a reality by nature and since time immemorial, constructionist approaches like those of Benedict Anderson and Ernest Gellner have insisted on its relatively recent political construction nature. Despite its unquestionable merits, this approach has often fallen into an excessively artificial perspective. According to it, the fabrication of any national identity would be possible with the appropriate skills to do so. Somehow, while essentialism refers to a metaphysical and substantivist, antidialectical approach, constructivism is very reminiscent of the old subjective idealism which believed that reality could be recreated by the individuals with almost complete liberty. For that reason, an approach like that of Lenin which conceives the national question as a long-term historical fact, and only politically manipulable to a very limited extent, could be of great use for materialist theoretical approaches. Some thinkers such as Maxime Rondinson and Pierre Vilar have shown this up.